Cultural preservations through digital reconstruction of Bytul Anwar, Kuala Kangsar, Perak, Malaysia - Abdul Majid, Noor Hanita; Denan, Zuraini (International Association of Computer Science and Information Technology Press (IACSIT), 2014)
Preservation of heritage building is one of the most important aspects in preserving the cultural identity of a nation. Therefore, the heritage buildings should be documented as it is to conserve old buildings for the future generation. Due to the current state of the heritage buildings and lack of funding many heritage buildings has been left dilapidated. Reconstructing buildings through digital media help to document and preserve the building virtually at minimum cost. The study was conducted on Bytul Anwar that has remained standing from 1912 until now and has undergone transition processes through time. Bytul Anwar was one of the palaces designed by Raja Harun Al-Rasyid who was the crown prince at that time. It is located in the royal compound of Bukit Chandan in Kuala Kangsar that consists of palaces and noble dwellings for the royal family of Perak. This paper presents digital reconstruction of Bytul Anwar and describes the morphology of the buildings from 1912 to 2010. The reconstruction of the heritage building is based on the following method; interviews, field measurements and computer graphic simulation to reconstruct the house in stages. The research has reconstructed the building digitally to document the additions and renovations including the changes in function of the palace through time. The digital media provides a sound background for documentation and further discussion in cultural heritage.